2017
DOI: 10.1501/vetfak_0000002802
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analysis of different fattening systems with Tuj and Hemşin lambs in controlled conditions

Abstract: Summary:This study aims to determine the most profitable fattening system through an economic analysis of lamb fattening in different fattening systems under controlled conditions which was performed for the first time in Turkey. The material of the study consists of 39 weaned lambs of 2.5-3 months old from each of the Tuj and Hemşin genotypes. In the study, the lambs were separated into the 3 fattening groups of extensive, semi-intensive and intensive including 13 Tuj and 13 Hemşin lambs in each group through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Nevertheless, care should be taken because this profit could be reduced drastically if the period of fattening exceeded the normal production cycle of two to four months due to increase in feeding costs without proportional increase in cattle size, indicating point of diminishing returns. Aydin et al (2017) in their study of Cost-benefit analysis of different fattening systems with Tuj and Hemşin lambs in controlled conditions reported that intensive system is the most profitable venture, followed by semi-intensive system and then extensive system. Similarly, Maloleet al, ( 2014) study two schemes of beef fattening scheme in Tanzania with scheme 1 fed on cottonseed hulls (CSHL) based diets and scheme 2 on cottonseed cake (CSC) based diets.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, care should be taken because this profit could be reduced drastically if the period of fattening exceeded the normal production cycle of two to four months due to increase in feeding costs without proportional increase in cattle size, indicating point of diminishing returns. Aydin et al (2017) in their study of Cost-benefit analysis of different fattening systems with Tuj and Hemşin lambs in controlled conditions reported that intensive system is the most profitable venture, followed by semi-intensive system and then extensive system. Similarly, Maloleet al, ( 2014) study two schemes of beef fattening scheme in Tanzania with scheme 1 fed on cottonseed hulls (CSHL) based diets and scheme 2 on cottonseed cake (CSC) based diets.…”
Section: Resultsmentioning
confidence: 99%